Relentless Individual and Collective Commitment: an Interview with Jaydeep Sarangi and Manohar Mouli Biswas. (21st August 2021) - Simon, Surya
Abstract: This interview with Indian translator, Professor Jaydeep Sarangi, and Indian writer, Manohar Mouli Biswas, was conducted on 16 th April, 2019 in New Alipore College, India; and was part of a series of interviews conducted for a doctoral project that examines caste system and Dalit experiences in the context of India. In this interview, Sarangi sheds light on his experiences as a translator of Indian narratives from Bengali to English. He talks in-depth about his passion for translating Dalit narratives and his relentless commitment towards studies on the Dalit subject. Biswas shares his arduous and inspirational experiences as a Dalit, as a writer, and as a social worker. He also explores the scope and possibilities offered through writing and translation, and what that means to the Dalit collective as well as the Indian society as a whole.